Charles Bonnet Syndrome: A Case Series from a Psychogeriatric Clinic in a Tertiary Hospital in Nigeria - Osundina AF; Fela-Thomas AL; Akanni OO; Olotu SO; Agbonile IO; Akpalaba RU (Annals of Psychiatry and Treatment - Peertechz Publications, 2017)
Charles Bonnet Syndrome (CBS), also known as visual release hallucinations is the experience of complex visual hallucinations in an individual with partial or severe blindness. It is an uncommon disorder with a worldwide prevalence ranging between 0.5%- 40%. However, the prevalence in Africa is largely unknown due to unavailability of reliable statistics. Furthermore, there has generally been an under-reporting of visual hallucinations by patients due to fear of being labeled psychologically unstable. As the population of old people increases in our society, there is also the likelihood of an increase in visual impairment among them and consequently an increase in those affected by CBS. We therefore report the two cases of this uncommon disorder that presented in our psychogeriatric clinic in order to raise awareness among clinicians with the aim of encouraging early detection and prompt treatment in a resource constrained setting like Nigeria.